Physico-Chemical Characterization and In Vitro Biological Evaluation of a Bionic Hydrogel Based on Hyaluronic Acid and l-Lysine for Medical Applications - Giuseppe Alonci; Roberto Mocchi; Sabrina Sommatis; Maria Chiara Capillo; Elsa Liga; Agata Janowska; Lidia Nachbaur; Nicola Zerbinati (MDPI AG, 2021)
Hyaluronic acid (HA) is an endogenous polysaccharide, whose hydrogels have been used in medical applications for decades. Here, we present a technology platform for stabilizing HA with a biocrosslinker, the amino acid L-lysine, to manufacture bionic hydrogels for regenerative medicine. We synthetized bionic hydrogels with tailored composition with respect to HA concentration and degree of stabilization depending on the envisaged medical use. The structure of the hydrogels was assessed by microscopy and rheology, and the resorption behavior through enzymatic degradation with hyaluronidase. The biological compatibility was evaluated in vitro with human dermal fibroblast cell lines. HA bionic hydrogels stabilized with lysine show a 3D network structure, with a rheological profile that mimics biological matrixes, as a harmless biodegradable substrate for cell proliferation and regeneration and a promising candidate for wound healing and other medical applications.